Reinhold Niebuhr papers - Niebuhr, Reinhold, 1892-1971.; Bingham, June, 1919-2007.; Niebuhr, Reinhold, 1892-1971.; Niebuhr, Reinhold, 1892-1971.; Niebuhr, Reinhold, 1892-1971.; Niebuhr, Ursula
Correspondence, speeches, sermons, lectures, typescripts of books and articles, book reviews, bibliographies, subject files, biographical material, family papers, photographs, memorabilia, and other papers relating chiefly to Niebuhr's influence on twentieth-century theology, politics, and society; and to his efforts to apply religious and ethical standards to modern social and political problems including labor and race relations. Documents his interest in the Delta Cooperative Farm Project, Hillhouse, Miss.; Committee on Economic and Racial Justice of the Socialist Party of Tennessee; U.S. National Committee for UNESCO; CARE Inc.; and other social agencies. Also documents Niebuhr's association with the Evangelical and Reformed Church; delivery of the Gifford lectures at the University of Edinburgh (1939); and travels to Germany with the U.S. Commission on Cultural Affairs in Occupied Territories (1946) and other trips to Europe in the 1940s.
Includes typescripts of three Niebuhr books: Man's Nature and His Communities: Essays on the Dynamics and Enigmas of Man's Personal and Social Existence (1965), Pious and Secular America (1958), and The Self and the Dramas of History (1955); and his book reviews in the New York Times, Saturday Review, and the New Republic. Also includes papers of Ursula Niebuhr relating, in part, to her work with the Jerusalem Committee; manuscript of June Bingham's biography of Reinhold Niebuhr, Courage to Change (1961); and papers relating to Richard Wightman Fox's Reinhold Niebuhr: A Biography (1985).
Correspondents include David H.K. Amiran, Ruth Amiran, W.H. Auden, John Barnes, Jacques Barzun, Tony Benn, John C. Bennett, Isaiah Berlin, Jonathan B. Bingham, June Bingham, Dietrich Bonhoeffer, Jimmy Carter, Tom C. Clark, Paul D. Clasper, Henry Sloane Coffin, James Bryant Conant, Isobel Cripps, Sir Richard Stafford Cripps, Sherwood Eddy, Dwight D. Eisenhower, T.S. Eliot, Felix Frankfurter, Sam H. Franklin, J. King Gordon, Ruth Anderson Gordon, Ronald O. Hall, Will Herberg, Hubert H. Humphrey, Robert Maynard Hutchins, George F. Kennan, Teddy Kollek, Franklin H. Littell, Archibald MacLeish, Norman Mailer, Martin E. Marty, George S. McGovern, Margaret Mead, Hans J. Morgenthau, Daniel P. Moynihan, H. Richard Niebuhr, Alan Paton, James A. Pike, Samuel D. Press, D.B. Robertson, Oliver W. Sacks, William Scarlett, Arthur M. Schlesinger (1888-1965), Arthur M. Schlesinger (1917-2007), Margaret Stansgate, Adlai E. Stevenson, Ronald H. Stone, Paul Tillich, Henry P. Van Dusen, Geraldine Van Husen, Hugh Van Husen, Willem Adolph Visser't Hooft, and E.L. Woodward. Organizational correspondents include Americans for Democratic Action, Commission on the Freedom of the Press, National Council of the Churches of Christ in the U.S.A., Union for Democratic Action, and World Council of Churches.
Library of Congress Prints and Photographs Division.
Theologian, philosopher, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Amiran, David H. K., -- 1910- -- Correspondence; Amiran, Ruth -- Correspondence; Auden, W. H. -- 1907-1973 -- Correspondence; Barnes, John, -- 1917-1992 -- Correspondence; Barzun, Jacques, -- 1907-2012 -- Correspondence; Benn, Tony, -- 1925- -- Correspondence; Bennett, John C. -- 1902-1995 -- Correspondence; Berlin, Isaiah, -- 1909-1997 -- Correspondence; Bingham, Jonathan B. -- Correspondence; Bingham, June, -- 1919-2007 -- Correspondence; Bonhoeffer, Dietrich, -- 1906-1945 -- Correspondence; Carter, Jimmy, -- 1924- -- Correspondence; Clark, Tom C. -- 1899-1977 -- Correspondence; Clasper, Paul D. -- Correspondence; Coffin, Henry Sloane, -- 1877-1954 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; Cripps, Isobel, -- 1891-1979 -- Correspondence; Cripps, Richard Stafford, -- Sir, -- 1889-1952 -- Correspondence; Eddy, Sherwood, -- 1871-1963 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Eliot, T. S. -- 1888-1965 -- Correspondence; Fox, Richard Wightman, -- 1945-; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Franklin, Sam H. -- Correspondence; Gordon, J. King -- Correspondence; Gordon, Ruth Anderson -- Correspondence; Hall, Ronald O. -- Correspondence; Herberg, Will -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Hutchins, Robert Maynard, -- 1899-1977 -- Correspondence; Kennan, George F. -- 1904-2005 -- Correspondence; Kollek, Teddy, -- 1911-2007 -- Correspondence; Littell, Franklin H. -- 1917-2009 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Mailer, Norman -- Correspondence; Marty, Martin E., -- 1928- -- Correspondence; McGovern, George S. -- 1922-2012 -- Correspondence; Mead, Margaret, -- 1901-1978 -- Correspondence; Morgenthau, Hans J. -- 1904-1980 -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Niebuhr, H. Richard -- 1894-1962 -- Correspondence; Paton, Alan -- Correspondence; Pike, James A. -- 1913-1969 -- Correspondence; Press, Samuel D. -- Correspondence; Robertson, D. B. -- Correspondence; Sacks, Oliver W. -- Correspondence; Scarlett, William, -- 1883-1973 -- Correspondence; Schlesinger, Arthur M. -- 1888-1965 -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Stansgate, Margaret, -- 1897-1991 -- Correspondence; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Stone, Ronald H. -- Correspondence; Tillich, Paul, -- 1886-1965 -- Correspondence; Van Dusen, Henry P. -- 1897-1975 -- Correspondence; Van Husen, Geraldine -- Correspondence; Van Husen, Hugh -- Correspondence; Visser 't Hooft, Willem Adolph, -- 1900-1985 -- Correspondence; Woodward, E. L. -- 1890-1971 -- Correspondence; Niebuhr family; United States. -- Commission on Cultural Affairs in Occupied Territories